THE INFLUENCE OF WORK MOTIVATION ON THE PERFORMANCE OF PUBLIC SERVICE EMPLOYEES IN PAGELARAN DISTRICT PANDEGLANG REGENCY - Teti Maryulina (Journal of Public Administration, 2023)
This study aims to determine the effect of work motivation on the performance of public service employees in the Performance Subdistrict, Pandeglang Regency. The sample in this study was all the village employees of Harapankarya and Karya Utama in the Performance Subdistrict, Pandeglang Regency. The sampling technique used in this study was based on the census sampling method, where all members of the population were sampled. The research approach used is descriptive-quantitative. Data collection techniques using a survey method in the form of a questionnaire The data analysis technique used is simple linear regression analysis and hypothesis testing using the SPSS for Windows Release 22 program. Based on the calculation results, if tcount > ttable is 4.133 > 2.073 and Fcount > Ftable is 17.085 > 4.320 with a significant level of 0.00 ˂ 0.05, then H0 is rejected and Ha is accepted, meaning that variable X (work motivation) has a positive effect on variable Y (employee performance). It can be concluded that work motivation partially has a significant effect on the performance of public service employees in the Performance Subdistrict, Pandeglang Regency. This shows that employee performance is determined by the level of work motivation possessed; the higher the work motivation, the higher the employee's performance.